RHETORICS IN KH ZAINAL ABIDIN MUNAWWIR'S 'WADHA’IF AL-MUTA’ALLIM' BOOK (RETORIKA DALAM KITAB 'WADHA’IF AL-MUTA’ALLIM' KARYA KH ZAINAL ABIDIN MUNAWWIR) - Fathur Rohman; Aan Wahyudin (UIN Raden Mas Said Surakarta, 2017)
This study is aimed at studying the book of Wadhaif al-Muta'allim written by KH. Zainal Abidin Munawwir by using Stylistics research approach. Stylistics is used to describe the elements of rhetoric in the book of Wadhaif al-Muta'allim, and its meaning effect. The method used is literature study in the form of semantic, thematic and descriptive analysis. Data is collected through text observation method known as simak methode. This study found that there were some rhetoric’s elements in the book of Wadhaif al-Muta'allim in the aspect of figure of speech, figure of tought, and imagery. The results also showed that the style of language had caused quite interesting interpretation of the educational tought contained in the book of Wadhaif al-Muta'allim.